Pembelajaran Tamadun Melayu Jambi Berbasis Outcome-Based Education (OBE) Berorientasi Produk Kreatif - Rustam Rustam; Priyanto Priyanto (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
The "Merdeka Belajar Kampus Merdeka" (MBKM) policy at the study program level requires analysis and mapping as well as the preparation of Outcome-Based Education (OBE)-based Graduate Learning Outcomes in the form of creative products that are in accordance with the competency demands of Subject Learning Outcomes. To implement the policy, an in-depth study is needed on implementing the Jambi Malay Tamadun learning course in the Indonesian Language and Literature Education study program in Jambi province. The research method uses mixed methods concurrent embedded design. Data were collected through interviews, observation, and documentation techniques for qualitative data, while quantitative data used an essay test. Based on the research results, PBSI lecturers have carried out: (1) analysis of outcomes-based curriculum (OBC), outcomes-based learning and teaching (OBLT), and outcome-based assessment and evaluation (OBAE), (2) analysis of CPL, (3) analysis of CPKM, (4) Sub-CPMK analysis, (5) reviewing study materials or materials, (6) implementing learning with the SCL approach, PjBL method, Case Method, contextual, and (7) assessing student learning outcomes in the form of creative souvenir product portfolios Jambi Malay traditional crafts.